2013
DOI: 10.1001/jamadermatol.2013.4256
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis and Psoriasis

Abstract: We report a case series of concomitant sarcoidosis and psoriasis, suggesting that common pathogenesis involving the T(H)1 and T(H)17 pathways may be responsible for this disease association. Although additional data are needed to clarify this association, this observation may lead to important understanding of the pathophysiologic and therapeutic management in these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Non-infectious granulomatous conditions such as granuloma annulare and sarcoidosis are rarely associated with psoriasis [98]. Th1 type cytokines are favored in the initial phase of sarcoidosis.…”
Section: Psoriasis and Granulomatous Diseasesmentioning
confidence: 99%
“…Non-infectious granulomatous conditions such as granuloma annulare and sarcoidosis are rarely associated with psoriasis [98]. Th1 type cytokines are favored in the initial phase of sarcoidosis.…”
Section: Psoriasis and Granulomatous Diseasesmentioning
confidence: 99%
“…Given the shared immunological pathways, coexistence of both conditions would be plausible as corroborated by reports and case series of patients with psoriasis and sarcoidosis 60 67–69Second, there is a paucity of clinical information on sarcoidosis, despite it being a multisystemic disease that can be debilitating and can result in morbidity if left untreated, that is, liver cirrhosis in patients with hepatic sarcoidosis and45 46 loss of vision in those with sarcoid uveitis 67. This lack of studies is particularly true for non-pulmonary and non-ocular sarcoidosis.We learnt important points about skeletal involvement of sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior studies have demonstrated increased levels of interleukin (IL)-17 in bronchoalveolar lavage fluid and peripheral blood in these patients [9] . In view of the apparent overlap of immunoinflammatory mechanisms, interest in a possible correlation between psoriasis and sarcoidosis was recently rejuvenated after publication of the as yet largest case series consisting of 7 patients with concurrent psoriasis and sarcoidosis [11] [13] . To the best of our knowledge, however, no large scale epidemiological study has previously been carried out to more definitively examine the association between these two diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the disease aetiology is poorly understood, the role of Th1- and Th17-mediated inflammation in formation of sarcoidal granulomas is well documented [8] – [10] . In view of this apparent pathogenic link between the two diseases it is interesting that limited case series have been presented with concurrent sarcoidosis and psoriasis [11] [13] . However, no large scale epidemiological data exist on this topic and we therefore examined the association between sarcoidosis and psoriasis, including the impact of psoriasis severity, in a nationwide cohort.…”
Section: Introductionmentioning
confidence: 99%